ROLE OF COMPUTED TOMOGRAPHY WITH PNEUMOGASTROGRAPHY IN DETERMINING THE REGRESSION GRADE OF LOCALLY ADVANCED GASTRIC CANCER AFTER NEOADJUVANT CHEMOTHERAPY - I. D. Amelina (Sibirskij Onkologičeskij Žurnal, 2021)
Introduction. A multimodal approach to the treatment of locally advanced gastric cancer with the addition of systemic or local treatment methods, such as chemotherapy and radiation therapy, reduces the risk of cancer recurrence, thus improving survival of patients. Advances in anticancer therapy dictate the need to develop systems for assessing tumor response to new treatment modalities.Material and Methods. The study included 162 patients with locally advanced gastric cancer who received treatment at the N.N. Petrov National Medical Research Center of Oncology from 2015 to 2018. All patients underwent subtotal gastric resection or gastrectomy with lymph node dissection and previously received neoadjuvant polychemotherapy. Patients were in the age range 30 to 80 years old. The tumor pathomorphological response to chemotherapy was assessed in all patients using a pathomorphological response rate system according to the classification of the Japanese Gastric Cancer Association (JGCA, 3rd English edition). All patients underwent computed tomography with pneumogastrography before neoadjuvant chemotherapy and immediately before surgery. For each of 162 patients, 96 qualitative and quantitative biomarkers of tumor and paragastric lymph node imaging were analyzed.Results. The accuracy of determining the tumor response rate using computed tomography with pneumogastrography was 82.6 % for TRG-0/1, 90 % for TRG-1/2, and 88 % for TRG-2/3. Discussion. The tumor pathomorphological response to treatment is a predictor of long-term results; however, it can be assessed only after analyzing the surgical specimen, and this marker cannot be used in inoperable cases and for correction of palliative chemotherapy. The study of imaging biomarkers based on quantitative and qualitative data reflecting the histopathological features of the tumor and lymph nodes can help determine the tumor regression grade and optimize treatment.Conclusion. The proposed algorithm for assessing the response grade of locally advanced gastric cancer to chemotherapy using imaging biomarkers is a promising prognostic marker and requires further study.